622 Applicability of duke activity scale index (DASI) in perioperative prediction of postoperative complications for gynaeoncology patients. (14th December 2020) - Sevinyan, Lusine; Tailor, Anil; Williams, Peter; Prabhu, Pradeep; Madhuri, Thumuluru Kavitha
Abstract : Introduction/Background: Cohort of patients with multiple comorbidities, obesity and frailty requiring gynaeoncological interventions is continuously increasing and because of that there is an unmet need for an accurate perioperative risk prediction. The Duke Activity Scale Index (DASI) is a 12 item self-reported questionnaire based around commonly performed activities. DASI score determines functional capacity through conversion to Metabolic Equivalent of task (METs), which have been shown to indicate fitness for surgery. In our study we continue to investigate the accuracy of DASI in prediction of postoperative outcomes in the context of gynaeoncology. Methodology: A retrospective data for 290 patients was collected using a dedicated gynaeoncology database or patients' notes at a tertiary oncology centre. All of the patients had filled the DASI questionnaire prior to surgery, which we used for the analysis. Actual postoperative complications which occurred within 30 days of the surgery were also recorded. The DASI score was then compared with the occurrence of postoperative complications. Results: According to our preliminary analysis of 141 patients DASI score has not found to be a statistically significant model for prediction of postoperative complications in the general population of the gynaeoncology patients (AUC-0.433). However we were able to show that a 25 point higher DASI score is predicted to deliver 1 day less in hospital. We also found that DASI score could be promising for patients with ovarian and cervical malignancy (AUC-0.634 and AUC 0.750 respectively), but there were not enough patients to validate the findings in the analysed cohort (figures 1 and 2 ). Conclusion: DASI is an uncomplicated and straightforward tool that could be useful in perioperative estimation of postoperative complications for ovarian and cervical cancer patients. Further analysis with a larger sample size and multicentre prospective study are currently underway to validate the findings. Disclosures: There are no disclosures to be made.